Are Mentally Disordered Offenders Admitted to Appropriate Secure Settings according to Security Needs? A Cross Sectional Study in Belgium. Issue 3 (17th November 2021) - Nicaise, Pablo; Bourmorck, Delphine; De Pau, Marjolein; Vander Laenen, Freya; Vanderplasschen, Wouter; Lorant, Vincent
Abstract: Mentally Disordered Offenders (MDOs) who have been declared not criminally responsible for their offense due to their mental condition should be admitted to settings with lowest possible level of security to support their social reintegration. In the context of the reorganization of care for MDOs in Belgium, we assessed the predictors and retrospective appropriateness of 3529 MDO admissions in 2017 according to security needs. Although there was a positive association between the security needs of MDOs and the level of security of the settings to which they were admitted, there was a gap between high and lower security levels. Medium-security settings made up 46% of all admissions, covering a variety of security need profiles. Half the sample of MDOs with high security needs was found in low- and medium-security settings, while a significant proportion of MDOs with low security needs was found in medium-security settings. Clinical characteristics predicted admissions more strongly than custodial characteristics. Decision-makers should refine criteria and procedures for MDOs' care access. Indeed, the mixed results in relation to admission appropriateness in medium-security services may result from the lack of formal guidelines.